Fire blight disease, a fast-approaching threat to apple and pear production in China - Yu-qiang ZHAO; Yan-li TIAN; Li-min WANG; Guo-min GENG; Wen-jun ZHAO; Bai-shi HU; You-fu ZHAO (Journal of Integrative Agriculture, 2019)
Fire blight, caused by Erwinia amylovora, is a devastating disease of apples and pears, causing enormous economic losses around the world. The disease is indigenous to North America and has spread to more than 50 countries since its discovery in 1870s. Recent reports of the disease in China's neighboring countries, including South Korea, Kyrgyzstan, and Kazakhstan, pose great threat to the world's leading producer of apples and pears. This mini-review intends to provide an update on the disease, pathogen biology, epidemiology, and control. It will also provide some perspectives and suggestions for the apple and pear industry and growers in China, which will face the imminent threat of this devastating disease.